JU_GERICHTE CON 2011 2 vom 1. September 2011 , Déclinatoire de compétence en faveur de la Cour des assurances - JU Tribunal cantonal (2011)
Déclinatoire de compétence en faveur de la Cour des assurances | conflit de compétence